The Challenges of Law Enforcement in Indonesia in Transforming Human Smuggling as Transnational Organized Crime - Siahaan, Herbin Marulak (International Journal of Psychosocial Rehabilitation, 2020)
In 2009, Indonesia ratified the United Nations Convention Against Transnational Organized Crime and Protocol Against the Smuggling of Migrants by Land, Sea and Air. By using juridical normative approach and case study, this research attempts to scrutinize international standards on People Smuggling and examine how Indonesian law enforcement have interpreted and applied standards in handling the people smuggling cases. It finds that the implementation of law enforcement in handling cases of people smuggling in Indonesia is still local and has not carried out international standards effectively. Therefore, the need for taking strategic and concrete efforts to transform people smuggling as transnational organized crime in law enforcement practices in Indonesia.